What is a “good” library? The measures are changing - Poll, Roswitha (Performance measurement and metrics, 2024)
PurposeStandardization of library performance measures started in 1994, when several handbooks describing performance indicators had already appeared. The 1st edition of the International Standard ISO 11620 was published in 1998, followed by an amendment 5 years later, both dealing with the traditional library. As indicators for the digital library services were still developing, a pre-standard technical report for such indicators was published separately in 2003. The second edition was published in 2008 and combined 45 indicators for traditional and digital services, if possible, as “hybrid” indicators. The 3rd edition appeared in 2013 with 52 indicators, presenting new topics such as preservation and digitization. For this edition, seven indicators had been eliminated as outdated. The 4th edition was edited in 2023, presenting 61 indicators, of which 14 new indicators and many revisions. The paper follows the subject areas and corresponding indicators over time and tries to define the present and possible future trends.Design/methodology/approachThe paper describes the development of library performance measurement as standardized in ISO 11620. It follows the changes, additions and deletions of indicators since the first edition in 1998 and compares them to the changes in libraries’ tasks and activities.FindingsThe analysis shows that indicators for changing tasks and technologies or for new fields of interest follow a few years after the changes, as the methods have to be developed and tested. New topics are often introduced from outside, following political trends and themes, such as cost-efficiency or support for special user groups. An important input came from other standards with quality indicators, especially ISO 21246 for museums and ISO 21248 for national libraries. An interesting issue is the changing role of indicators for the digital library in ISO 11620. Until the forthcoming edition, a simple increase in digital collections and services was often regarded as quality. The new concept is to regard the existence of digital services and collections in libraries as normal and to look for additional aspects, e.g. the use of a digitized collection.Research limitations/implicationsFor the first time, the forthcoming edition will contain a clause about impact assessment. Measuring the quality of library services should not stop with effectiveness and efficiency but should also include assessing the impact on individuals and society. Methods for assessing library impact are described in a separate standard, ISO 16439. However, there is evidently a borderland between evaluating the quality of library services and identifying their effect on users. The new edition of ISO 11620 tries to clarify this and includes some “border” indicators, such as measures for the awareness of libraries their services.Originality/valueThe overview of developments in the standardized performance measures will help to understand the relation of the indicators to the current goals and tasks of libraries and may further the use of the standard. As libraries’ tasks and activities will continue to develop and change, new topics will come up in the next few years, some of which can already be identified today.